Characteristics of Mechanical Strength of Hybrid Reinforced Plastic Waste Mixed with Wood Waste - Jamal, I. I; Marsi, N; Letchumanan, T; Mohd Rus, A. Z; Hashim, M. M (ump, 2024)
Commercial products made of plastics or wood have always been in high demand until now. Consequently, waste from these products has increased, accumulated, and catastrophically impacted the environment. Through recycling, waste products are not only reduced but will also be easily available for improvement or manufacturing new products. This research focused on the fabrication of lightweight composites using plastic waste (PW) and wood waste (WW) as reinforcement and epoxy as a matrix suitable for tile applications. It was revealed that the density of PW-WW polymer composite increased with increasing PW loading up to a 4.0 ratio at 1.070 g/cm3 with a porosity of 0.05%. Optical microscope analysis at 100X magnification showed good bonding between the reinforcements (PW and WW) and matrix (epoxy). With a maximum bending strain of 2.41%, the 3.0 ratio achieved the highest bending strength of 2069.20 N, followed by the bending stress at 8.28 MPa. The PW-WW polymer composite with a composition ratio of 3.0 showed a maximum tensile force of 313.8 N and a tensile strength of 1.79 MPa. The composite with a 4.0 ratio had the greatest impact strength (1.67 kJ/m²), followed by the composite with a 3.0 ratio (1.44 kJ/m²). In summary, a 3.0 ratio is the best polymer composite composition for tile applications.